A Reflection on Precarity - Babb, Maureen (Partnership, 2021)
This personal reflective piece explores precarity in academic libraries from the perspective of someone who has been a precariously employed librarian, but has shifted to more stable employment. The detrimental aspects of precarious work are explored, both in relation to individuals and in relation to the institutions that hire precariously. There is discussion of the lack of attention paid to this critical topic, and a call for those with secure positions to turn their attention towards the problem of precarity in libraries.